THE DEVELOPMENT OF THE SENI CINTA WEBSITE, INCORPORATING METICULOUS PROCESSES IN DESIGN, DEVELOPMENT, AND THOROUGH EVALUATION OF USER EXPERIENCE - T Zalizam T Muda; Nurul Shafikah Mohamad, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This in-depth investigation delves into the evolution of the web for the "Seni Cinta" book, also known as "Love Uses the Brain" in English. Seni Cinta is a digital platform in the Malay language that is dedicated to unravelling the intricate facets of love and love languages within various relationships, including those in families and friendships. Beyond static content, the website enriches user engagement by incorporating five unique personality tests, offering individuals profound insights into their distinct characteristics. Utilising the user-friendly WordPress platform, the website is a custom creation that does not require coding expertise. The primary aim of this study goes beyond exploration; it positions the website as a strategic tool to enlighten the target audience about their individual love personality types. Additionally, the website serves as a promotional gateway for the company's upcoming book, "Cinta Pakai Otak". To simplify the user experience, the platform facilitates seamless book orders, eliminating the need for prolonged account registrations and prioritising accessibility and efficiency. The methodology of the study unfolds through several phases, starting with the requirement phase and progressing through design, development, testing, and deployment, culminating in an ongoing maintenance phase. Client satisfaction with the Seni Cinta website validates the achievement of the primary goal: designing an interactive and user-friendly digital space. The successful integration of informative content, personality assessments, and streamlined book promotion underscores the effectiveness of this comprehensive approach, demonstrating its relevance in meeting the evolving needs of a diverse audience navigating the complexities of love and interpersonal dynamics.